Morphological changes in gametes of tiger barb Puntius tetrazona (Cypriniformes: Cyprinidae) and the implementation of in vitro fertilization - Domínguez-Castanedo, Omar; Toledano-Olivares, Ángel; Martínez-Espinosa, David; Ávalos-Rodríguez, Alejandro (Revista de Biología Tropical, 2014)
The production of ornamental fishes represents an economic activity of a growing number of Mexican families. Nevertheless, the reproduction of fish in captivity is one of the complications faced by farmers. This study was set up to: (i) evaluate the morphological and functional changes induced by hydration in the gametes of fish tiger barb (Puntius tetrazona; 240 samples) at tree times after hydration (10, 20 and 30s) with classic spermograms (volume, sperm concentration, viability, motility, and normal morphology); and (ii) evaluate the implementation of in vitro fertilization based on the ovulation rate, the percentage of fertilization and hatching, and the larval numbers obtained after 72 hours. The average volume of milt was 3.0±0.7μL, and the minimum, maximum and average concentration of sperm was 44.4x106 spz/mL, 52.3x106spz/mL, and 48.1±5.9x106spz/mL, respectively. The viability and motility of the sperm was 84.6±3.2% and 81.5±2.2%, respectively. The diameter of the sperm with/without water contact was 2.1±0.6μm and 3.8±1.0μm (p<0.05); the largest diameter was recorded 30 seconds after the contact with water. For oocytes, the smaller and larger diameters were recorded at 10 and 30s, respectively (both with/without water contact); the oocytes diameters after 10 and 30 seconds of contact with water were 1.11 and 1.55mm, respectively. A higher ovulation rate was recorded using the in vitro fertilization: 250±50 oocytes versus 28±09 oocytes (during natural fertilization; p<0.05). Nevertheless, fertilization and hatching rates were higher for the natural fertilization (80 and 60%, respectively). Considering the number of larvae obtained after 72 hours, our results showed a higher value for the in vitro fertilization (75±18 compared to 13.4±12 of the natural fertilization; p<0.05). We propose this fish as a model for other ornamental fishes of commercial interest. Our results demonstrate that the in vitro fertilization is a very high viable option to optimize and maximize resources; besides, the reproduction management optimization under controlled conditions may enhance wild fish stocks preservation.